Over 2.7 million Africans accessed High-Iron Beans (HIB) through school meals in 2024 - Munthali, Justice; Munyangeri, Yvonne Uwase; Radegunda, Kessy Francis; Kajunju, Napoleon Heri Bahati; Mabeya, Justin Machini; Birachi, Eliud Abucheli; Rubyogo, Jean Claude (2025)
High-iron beans (HIB) reached additional 2,766,409 people across, the Democratic Republic of Congo, Kenya, Malawi, Rwanda, and Tanzania, and through school meal programs. This expansion builds upon a 2023 Pan-Africa Bean Research Alliance (PABRA) Outcome Impact Case Report, which highlighted the success of the Improving Bean Production and Marketing in Africa (IBPM) project, increasing HIB consumers from 720,000 to 22.14 million since 2019 [1]. This impact is driven by broader HIB promotion and adoption among non-PABRA stakeholders.